(untitled) (TAMADDUN NURI JURNALI, 2025)
The article scientifically substantiates the socio-philosophical views of Michel de Montaigne. “Thinkers of the Enlightenment, who made the “revival” of Greco-Roman culture their main task and sought to feed it with the achievements of their own late medieval civilization, carried out an organic synthesis of humanistic Christian faith and ancient wisdom”. The rebellion against dogmatism in the philosophy of Michel de Montaigne is an expression of the desire of not only the thinker of his time, but also a high-ranking statesman to remove obstacles to social development. Currently, in Uzbekistan, there is an urgent need for such ideas from scientists.